How Millennials Make Investment Decisions: Financial Literacy and Financial Behavior - Tamara, Dewi; Maharani, Anita (UI Scholars Hub, 2024)
This study investigates the effect of financial literacy, financial attitude, risk perception, and financial behavior on investment decisions. Employing a survey method with 342 respondents in Jakarta, the findings reveal that financial literacy has a negative and insignificant effect on investment decisions. In contrast, risk perception plays a crucial role in influencing investment decisions. Furthermore, financial behavior has an indirect mediating effect between financial literacy and risk perception on investment decisions but does not affect financial attitude. This study concludes that risk perception and financial behavior are important factors in investment decisions. Future research may consider incorporating other variables such as herding behavior or overconfidence.